Relationships between hydrodynamics and rheology of flocculating yeast suspensions in a high-cell-density airlift bioreactor - Klein, Jaroslav (2005)
In this article a hydrodynamic and rheological analysis of a continuous airlift bioreactor with high-celldensity system is presented. A highly flocculating recombinant strain of Sacharomyces cerevisiae containing genes for lactose transport (lactose permease) and hydrolysis (β-galactosidase) was exploited to ferment lactose from cheese whey to ethanol. The magnetic particle-tracer method was used to assess the effect of operational conditions (air-flow rate, biomass concentration) on hydrodynamic behavior of an airlift bioreactor during the fermentation process. Measurements of liquid circulation velocity showed the existence of a critical value of biomass concentration at which a dramatic deceleration of net liquid flow appeared with increasing biomass quantity. Rheological analysis revealed exponential increase of viscosity of the yeast floc suspension at the same biomass concentration of about 73 g/dm³ corresponding to 42.8% v/v of solid fraction. These facts have a particular importance for the successful processing of a high-celldensity airlift bioreactor as only a circulated flow regime will be favorable to keep the solid particles in suspension state and evenly distributed throughout the bioreactor.